2018
DOI: 10.20547/jms.2014.1805105
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Emotion Theory and Emotion-Action Tendency in Online Impulsive Buying Behavior

Abstract: Impulsive buying in online setting has become an epidemic as it represents a noteworthy proportion of online shopping. Impulsive buying behaviors with upcoming avenues for future research are under the constant considerations of academicians and practitioners. Despite abundant research on impulsive buying behavior in online context, research scholars demand for further research and empirical evidences for better understanding of the phenomenon. It is therefore worthy question to examine impulsive buying behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 43 publications
1
23
3
2
Order By: Relevance
“…Wu et al (2016) posited that consumer trust could trigger impulsive buying. Habib and Qayyum (2018) examined that the enhanced perceived trust will stimulate impulsive purchasing behavior by increasing emotional response. Yi and Jai (2020) confirmed that the sense of trust can trigger consumers' impulsive buying.…”
Section: Consumer Trust and Impulsive Buying Behaviormentioning
confidence: 99%
“…Wu et al (2016) posited that consumer trust could trigger impulsive buying. Habib and Qayyum (2018) examined that the enhanced perceived trust will stimulate impulsive purchasing behavior by increasing emotional response. Yi and Jai (2020) confirmed that the sense of trust can trigger consumers' impulsive buying.…”
Section: Consumer Trust and Impulsive Buying Behaviormentioning
confidence: 99%
“…Previous research on shopping websites has revealed that the informativeness of a website positively influences consumers’ emotional responses [ 64 ]. Majumdar and Bose [ 13 ] also demonstrated that charitable crowdfunding fundraisers use detailed information to emphasize their needs and suffering to attract others’ attention.…”
Section: Introductionmentioning
confidence: 99%
“…They are also supposed to follow a balanced approach in their consumption patterns and avoid from wasteful and excessive consumption ( Ghani, Harjin, & Ghani, 2008). Impulsive buying is recognized as the sudden and hedonically complex purchases which require instant ownership of an item (Attiq, 2015;Chan et al, 2017;Habib & Qayyum, 2018). Rook (1987) postulated that different people show various tendencies for impulse buying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Marketers are continuously involved in stimulating consumers during their purchase process to facilitate their decision making. Impulsive buying being a latent half of consumer behavior represents a sizeable amount of purchases (Habib & Qayyum, 2018). Research studies revealed the fact that 70% of decisions are made at point of purchase (Hulten & Vanyushyn, 2011).…”
Section: Introductionmentioning
confidence: 99%